Experimental Studies on Mechanical and Thermal Properties of Polyester Hybrid Composites Reinforced with Sansevieria Trifasciata Fibers. (12th July 2022) - Premkumar, R.; Sathish Kumar, K.; Maniraj, J.; Felix sahayaraj, A.; Jenish, I.; Hussain, Fayaz; Khedher, Nidhal Ben; Aich, Walid; Suresh, V.
Abstract : In the recent decades, natural fiber reinforced composite (NFRC) plays a vital role in most of the engineering applications including automobile and structural. The demand for novel natural fiber increasing steeply in recent times. Current research work aimed to develop hybrid sansevieria trifasciata fiber (HSTF)/polyester composite, and researchers combined untreated sansevieria trifasciata fibers (USTFs) with NaOH treated sisal fibers (NSTFs) and combined them with a polyester matrix. The reinforced effect of HSTFs was shown to be superior to that of NSTFs. It has the tensile strength of 48.47 MPa, the flexural strength of 69.17 MPa, and the impact strength of 16.34 kJ/m 2 . The thermal behaviour of the composite increased because of chemical treatment and hybrid composition. Polyester/HSTFs show superior mechanical properties compared to other developed samples.